COMPARATIVE STUDY OF THE THERMAL EFFECT OF TWO KINDS OF OPTIC FIBRES OF HIGH INTENSIVE 810 NM DIODE LASER (IN VITRO STUDY) - Raya Grozdanova-Uzunova; Elka Radeva; Dimitar Kosturkov; Evgeniya Popova; Tsonko Uzunov (Peytchinski Publishing, 2021)
Purpose: The aim of our in vitro study is to investigate the thermal changes on the outer root surface that occur after irradiation with a high intensive diode laser with two types of optical fibers. Material and Methods: The root canals of 24 extracted single-rooted and multi-rooted teeth (59 root canals) were prepared with Pro Taper Gold to F3 and treated with 810 nm diode laser for 8 s with circular movements from apex to orifices. Teeth are divided into two groups. A quartz light guide is used in the first group, and in the second group, the root canals are treated with an organically modified quartz light guide. The temperature changes were detected with FLIR - Т 330 Infrared Thermal Camera and the data was processed with FLIR Reporter 9 Professional software. Results: In 90% of cases, the temperature rise on the outer root surface is up to 8°C. In the first group with quartz fiber, the minimum increase in temperature is 2°C, the maximum is 11°C (in the cases with four root canals). When using the organically modified quartz fiber, the registered minimum increase in temperature is 1.2°C and maximum increase of 9.2°C (in cases with curved canals). Conclusion: Temperature changes on the outer root surface using an 810 nm diode laser are biocompatible. There is no statistically significant difference between the temperatures measured in the two types of optical fibers used - quartz and organically modified quartz light.